Factors Associated With Retained Foreign Bodies Following Major Operations. Issue 10 (October 2021) - Verma, Arjun; Tran, Zachary; Hadaya, Joseph; Williamson, Catherine G.; Rahimtoola, Rhea; Benharash, Peyman
Background: Retained surgical foreign bodies (RFB) are associated with inferior clinical and financial outcomes. The present work examined a nationally representative sample of all major operations to identify factors associated with RFB. Study Design: The 2005-2017 National Inpatient Sample was used to identify adults undergoing cardiac, neurosurgical, orthopedic, genitourinary, gastrointestinal, vascular, and thoracic operations. International Classifications of Diseases 9th-10th Revisions diagnosis codes were used to identify instances of RFB. Results: Of an estimated 71, 445, 042 hospitalizations, .02% had a diagnosis of RFB, with decreasing incidence from .03 to .02% over the study period (NPtrend < .001). Relative to vascular operations, gastrointestinal (adjusted odds ratio [AOR] 2.12), thoracic (AOR 1.80), and multi-cavity (AOR 2.17) were associated with greater odds of RFB. Laparoscopic approach (AOR .33) and trauma-associated admission (AOR .52, all P < .001) were associated with reduced odds of RFB. Despite similar mortality, RFB was associated with increased odds of pulmonary infection (AOR 1.62), sepsis (AOR 1.26), and wound infection (AOR 5.15), as well as a 2.3-day increment in length of stay and $7700 in hospitalization costs (all P < .001). Conclusion: The development of novel mitigation strategies may reduce the incidence of RFB in high-risk populations, such as those undergoing gastrointestinal, thoracic, and multi-cavity operations.